2018
DOI: 10.1007/s00702-018-1891-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield atrophy in patients with Parkinson’s disease and psychosis

Abstract: Psychosis, manifested through formed visual hallucinations or minor hallucinations, is a common non-motor symptom of Parkinson's disease (PD). The pathogenesis of psychosis in PD remains unclear; however, is possibly linked to structural and functional alterations in the hippocampus. To explore the role of hippocampus in psychosis, a detailed hippocampal subfield analysis was performed on PD patients with (PD-P) and without psychosis (PD-NP), and healthy controls (HC). An automated subfield parcellation was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Therefore, the increased bilateral hippocampal fissure volume observed in SA may imply impending whole hippocampus atrophy. This kind of lesion has also been reported in patients with first-episode schizophrenia [42], Alzheimer's disease [43][44][45], and Parkinson's disease [46], which is consistent with disrupted neurodevelopment in this brain region. Longitudinal studies are needed to follow the possible secondary reduction in hippocampal volume caused by hippocampal developmental disruption that happened in early life.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the increased bilateral hippocampal fissure volume observed in SA may imply impending whole hippocampus atrophy. This kind of lesion has also been reported in patients with first-episode schizophrenia [42], Alzheimer's disease [43][44][45], and Parkinson's disease [46], which is consistent with disrupted neurodevelopment in this brain region. Longitudinal studies are needed to follow the possible secondary reduction in hippocampal volume caused by hippocampal developmental disruption that happened in early life.…”
Section: Discussionsupporting
confidence: 80%
“…The diagnosis of idiopathic PD was based on the UK Parkinson's Disease Society Brain Bank criteria (Hughes, Daniel, Kilford, & Lees, ) and confirmed by a trained movement disorder specialist (author PKP). Patients included in this study have been part of other studies (Lenka et al, ; Shah et al, ) from this group and all patients and controls provided informed consent prior to recruitment in the original projects. Data usage for this study was reviewed and approved by the review board at NIMHANS.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, an integrated model for visual hallucinations occurrence has been proposed, including impaired visual input and visual processing, reduced control on the sleep–wake cycle by the brain stem, cognitive dysfunction, and influence of dopaminergic drugs . In treated PD patients with visual hallucinations, structural MRI studies showed reduced GM volume in the visual associative areas, including the lingual gyrus and superior parietal regions, but also in the hippocampus and temporal cortex . Moreover, in these patients, Bejr‐Kasem and colleagues demonstrated the presence of an aberrant functional connectivity between posterior regions of the default mode network and the visual‐processing area.…”
Section: Resultsmentioning
confidence: 99%